THE EFFECT OF SEVERAL TOOTHPAST ON THE GROWTH OF Streptococcus mutans - Nawaly, Hermanus; Pagaya, Joseph; Kaihena, Martha (RUMPHIUS, 2020)
This study aims to determine the effect of several toothpastes on the growth of Streptococcus mutans which is the main cause of tooth decay. The study used 5 types of toothpaste, namely toothpaste A, toothpaste B, toothpaste C, toothpaste D, and toothpaste E. The antibacterial testing method used the diffusion method with the cup-plate technique. The significance level of each type of toothpaste was measured using a completely randomized design followed by a Tukey test to see differences in toothpaste treatment. The results showed that toothpaste A with active ingredients Monofluorophosphate Sodium 1.12%, Triclosan 0.3%, Calcium Glycerophosphate 0.13% had the largest average resistance zone of 27.3 mm. Whereas Toothpaste E with the active ingredient 0.08% Sodium Monofluorophosphate, 0.01% Sodium Fluoride has the smallest average resistance zone, which is 14.25 mm. The diameter of the ANOVA test zone of several types of barrier toothpaste against Streptococcus mutans at 95% confidence intervals showed that there was a significant difference.